Islamic Law Enforcement Through Religious Courts in Indonesia - Enden Haetami (Global Writing Academica Researching & Publishing, 2019)
As a country with the largest Muslim community in the world, the existence of Religious Courts is quite important as a step for the Islamic community to obtain justice. This research then aims to see how the position, authority and legal sources of the Religious Courts are in becoming Islamic law enforcers in Indonesia. This research is qualitative research using data from previous studies. The results of this study found that the source of law owned by the Religious Courts comes from material sources of law, such as Islamic law, and formal sources of law originating from statutes. Then, the Religious Courts have the ability to evaluate, decide, and resolve a variety of disputes at the initial level involving Muslims. The authority of the Religious Court itself is comprised of both relative and absolute authority.